2018
DOI: 10.4314/jfas.v9i6s.97
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between leadership style and performance of Perak SUKMA athletes and coaches

Abstract: The purpose of this study was to examine the relationship between leadership style and performance of athletes and coaches in Malaysia. One hundred and thirty seven athletes and 47 coaches from 12 sports participated in the study. Leadership Scale for Sport (LSS) questionnaire was utilized to assessed athletes' preference, perceived and coaches' perception of their own leadership style. Result showed athletes most preferred coaching styles were training and instruction followed by democratic, positive feedback… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
(12 reference statements)
1
5
0
Order By: Relevance
“…Coaches can help the athlete with their problems, congratulating the athlete after performing games and adapting the coach leadership style. Moreover, this research result supported by Chee, Rasyid, Tengah et al (2017) showed that female athletes perceived training and instruction coach leadership styles more than male athletes. These findings suggested that coaches should apply different coach leadership styles for both genders in male and female athletes.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…Coaches can help the athlete with their problems, congratulating the athlete after performing games and adapting the coach leadership style. Moreover, this research result supported by Chee, Rasyid, Tengah et al (2017) showed that female athletes perceived training and instruction coach leadership styles more than male athletes. These findings suggested that coaches should apply different coach leadership styles for both genders in male and female athletes.…”
Section: Discussionsupporting
confidence: 65%
“…According to research, Nizam, et al (2016) found that the athletes most preferred coach leadership styles are Positive feedback. This statement contradicts Chee et al (2017) who found that the most perceived coach leadership style was autocratic style. However, an autocratic coach makes decisions independently and working stresses personal authority while working with the decision making.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations